2014
DOI: 10.1073/pnas.1405005111
|View full text |Cite
|
Sign up to set email alerts
|

Automodification switches PARP-1 function from chromatin architectural protein to histone chaperone

Abstract: Poly [ADP-ribose] polymerase 1 (PARP-1) is a highly abundant chromatin-associated enzyme. It catalyzes the NAD + -dependent polymerization of long chains of poly-ADP ribose (PAR) onto itself in response to DNA damage and other cues. More recently, the enzymatic activity of PARP-1 has also been implicated in the regulation of gene expression. The molecular basis for the functional switch from chromatin architectural protein to transcription factor and DNA damage responder, triggered by PARP-1 automodification, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
117
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(131 citation statements)
references
References 43 publications
8
117
1
1
Order By: Relevance
“…Elegant work from the Luger lab indicated that PARP-1 had histone chaperone function (58). This action of PARP-1, in principle, could modulate ABCA1 expression by facilitating a less open and more repressive chromatin state that precluded LXR binding.…”
Section: Discussionmentioning
confidence: 99%
“…Elegant work from the Luger lab indicated that PARP-1 had histone chaperone function (58). This action of PARP-1, in principle, could modulate ABCA1 expression by facilitating a less open and more repressive chromatin state that precluded LXR binding.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, there was no association between NACT and PARP-1 IHC staining, but this may of course be due to a smaller sample size in our study or to differences in the antibodies used. In our study, we used an antibody recognizing highly conserved PARP-1 C-terminus containing the catalytic domain [41] instead of N-terminal domain [26]. As discussed before, the weakness of PARP-1 IHC seems to associate with its dependency on researcherrelated methodological factors such as the antibody used, staining protocol and data analysis.…”
Section: Discussionmentioning
confidence: 99%
“…PARP-1 binds to nucleosomes by recognizing specific structural features (Kim et al 2004) and can alter nucleosome structure while binding cooperatively with transcription factors, such as the pioneer transcription factor Sox2 (Liu and Kraus 2017). Finally, PARP-1 can also function as a histone chaperone by directly binding or recruiting other factors to facilitate nucleosome assembly (Muthurajan et al 2014).…”
Section: Parps In Gene Regulation: a Focus On Parp-1mentioning
confidence: 99%